PERTUMBUHAN EKONOMI DAN STRUKTUR RUANG STUDI KASUS KAWASAN METROPOLITAN SARBAGITA - sinang ika syifa; Harsanto Nursadi; Sutanto Soehodho (Epigram, 2025)
Economic growth is one of the indicators to analyze economic development that occurs in a region. The increasing population in a region has implications for the expanding urban development area, so that the spatial structure of the region is widening. The spatial structure of a region is also influenced by changes in GRDP (Gross Regional Domestic Product) to measure the economic level of a city. The purpose of this study is to analyze the spatial structure and economic growth in the SARBAGITA Metropolitan Area. This study uses GRDP data for 2012-2022, LQ and Shift Share analysis used to identify leading sectors and changes in economic growth. The results showed that the wholesale and retail trade sector, the accommodation and food services sector, the construction sector, and the information and communication sector were the main drivers of economic growth in the region. Denpasar City and Badung Regency as the main growth centers experienced a significant increase in population. Rapid economic growth has changed the spatial structure of the region, marked by urbanization and changes in land use from agriculture to residential and commercial. The results of this study indicate a positive correlation between economic growth and changes in spatial structure. The implication of this study is the importance of comprehensive spatial planning to anticipate population growth, maintain environmental balance, and support sustainable development in this metropolitan area.